Correlation of Operational Verbs with Formulating Hots Indicators in the Plan Implementation of Student Learning - Tepu Sitepu; Mhd Isman (Budapest International Research and Critics University, 2022)
Globalization in the field of education needs to be considered so that the results of national education can compete with developed countries. The management and implementation of education is directed by the Government and the House of Representatives by Law Number 20 of 2003 of 2003 concerning the National Education System and Government Regulation Number 19 of 2005 concerning National Education Standards. PP Number 25 of 2000 Article 2 paragraph (2) states that the Central Government has the authority to develop curriculum and assessment of learning outcomes nationally. These laws and government regulations are the background of this research. The purpose of this study was to determine the correlation of understanding the concept of Cognitive and Psychomotor Operational Verbs with the Formulation of HOTS- based Competency Achievement Indicators in the Learning Implementation Plan (RPP) Indonesian Language Education Students Faculty of Teacher Training and Education, University of Muhammadiyah North Sumatra Sixth Semester Academic Year 2020-2021. The research method used is Descriptive Explorative Development Research (DEDR). The number of research samples is 41 sixth semester students of the Indonesian Language Education Study Program. The results of the Explorative Descriptive or Pretest study obtained an average understanding of cognitive and psychomotor operational verb concepts = 41.83 and the average value of the formulation of indicators of competency achievement = 58.53. The results of the Descriptive Development or Posttest study obtained that the average value of understanding the concept of cognitive/psychomotor operational verbs was 52.07 and the average value of the formulation of indicators of competency achievement in lesson plans was 75.61. The correlation coefficient value in exploratory descriptive research was 0.45 (category). Weak) and the value of the correlation coefficient in descriptive development research is 0.46 (weak category). Thus, the results of this study can be concluded that if the understanding of the concept of cognitive/psychomotor operational verbs based on Higher Order Thinking Skills is weak, then the formulation of indicators of achievement of competence based on Higher Order Thinking Skills in the Learning Implementation Plan is also weak. Therefore, intensive training is needed from lecturers and students themselves.